Predicting weld root notch stress intensity factors for rib-to-deck welded joint under deck loading modes. (November 2019) - Luo, Pengjun; Zhang, Qinghua; Bao, Yi
Highlights: The effects of the geometrical parameters on the weld root NSIFs of the rib-to-deck welded joints is investigated. Multi-parameter analysis is carried out to propose the formulae of predicting the weld root NSIFs. The proposed NSIFs formulae are applied to evaluate the stress distributions and averaged SED of the fatigue test specimens. The predicted averaged SED is used to link the fatigue test data to the W-N curves. Abstract: Orthotropic steel deck (OSD) has been widely employed in the bridge engineering owing to its superiorities of light-weight and high strength. However, the fatigue damage of rib-to-deck welded joint in OSD is one of the most challenging issues. The notch stress intensity factors (NSIFs) that characterize the local mechanical properties of notch tips are major parameters for fatigue evaluation of rib-to-deck welded joint. This paper proposes formulae of the NSIFs of weld root for rib-to-deck welded joint under deck loading modes. First, parametric studies are conducted using a finite element model to establish a holistic understanding of the effects of the geometrical parameters on the NSIFs. The investigated parameters include the weld penetration rate, relative weld height, deck toe flank angle, and plate thickness ratio. Then, multi-parameter analysis is carried out based on the data generated from the parametric study. Finally, the proposed formulae of the NSIFs are evaluated and applied to evaluate the stress distribution and the averaged strain energy density of single-weld specimens for rib-to-deck welded joints. The maximum error of 9.5% indicates that the NSIFs predicted using the proposed formulae are in good agreement with the finite element analysis results. The proposed formulae provide useful tools for determining the stress distributions and the averaged strain energy density of single-weld rib-to-deck welded joint specimens.